The Impact of a Legally Flawed Court Decision on a Good and Healthy Environment for the Awyu Tribe (Study of Decision Number 6/G/LH/2023/PTUN.JPR) - Pangastuti, Dimas; Kusumawati, Erna Dyah (Dinasti Research, 2025)
The 5th rank held by Indonesia regarding the number of children with stunted growth is a reflection of the unfulfilled right to a good and healthy environment for the community, healthy and cheap food and adequate nutrition for pregnant women. The State's obligation to guarantee the fundamental rights of Indonesian citizens as mandated by the constitution Article 28 H Paragraph 1 of the Constitution of the Republic of Indonesia tends not to be felt, especially by people living in remote lands of Indonesia, especially Papua. This article will analyze whether in substance the environmental impact analysis document of PT. Is Indo Asiana Lestari in line with the laws and regulations in Indonesia? In addition, the Potential Impact of the Legitimacy of the Environmental Impact Analysis Document on Substance Defects through Decision Number 6/G/LH/2023/PTUN. JPR? In the discussion section, it will be examined in depth regarding the alignment between the substance of the AMDAL of PT. Indo Asiana Lestari with environmental regulations in Indonesia and how the potential impack of the Jaya Pura PTUN decision Number 6/G/LH/2023/PTUN. JPR for the right to a healthy environment of the Awyu Tribe. This research is a normative research using the library research method to examine legal materials, legal principles to answer the legal issues faced. This type of research is qualitative descriptive. The research approach used is a statute approach to study and study all laws and regulations related to legal issues regarding the harmonization of environmental impact analysis documents of PT. Indo Asiana Lestari with environmental regulations in Indonesia and the potential impact of the Legitimacy of the Substance Defect Environmental Impact Analysis Document through Decision Number 6/G/LH/2023/PTUN. JPR